ETNOGRAFI SENI PERTUNJUKAN RITUAL DI KABUPATEN SUMEDANG - Dede Suryamah (LP2M ISBI Bandung, 2016)
This article is an ethnographic stud that explores the phenomenon of performing arts which functioned as a means of rituals in the society. The assumption ocused in this paper is the social fact that the inception of a culture work in society can not be separated from the historical background of the community. To uncover the truth of this assumption, Sumedang area is selected as an area that presumably has the potentials of rituals culture which still alive today. In the midst of today's socio-cultural changes with a mind set oriented on logical and objective thinking, in Sumedang society, there are still some arts oriented on non-logical and subjective thinking such as the arts that serves as a means of rituals. Associated with the existence of these arts, through ethnograp hic studies it will be revealed the historical background of belief system in the Sumed ang society, rituals performing arts in the Sumedang community, and the types of today's arts used for ritual performances.